Prediction of major adverse cardiovascular events following ST-segment elevation myocardial infarction using cardiac obesity marker—epicardial adipose tissue mass index: a prospective cohort study - Liu, Zeyan; Wang, Jinbo; Yang, Yanfang; Cheng, Jinglin; Yang, Min; Zhang, Ye (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAlthough reperfusion therapy has led to improvements in the acute phase of ST-segment elevation myocardial infarction (STEMI), the incidence of major adverse cardiovascular events (MACE) following STEMI has not significantly decreased. The accumulation of epicardial adipose tissue (EAT) may be associated with poorer STEMI prognosis and could serve as a potential prognostic marker. However, research examining this relationship remains limited.MethodsThis single-center prospective study enrolled 308 STEMI patients. Patients were randomly assigned to training set and validation set in a 7:3 ratio. The primary outcome was MACE one-year post-STEMI. Epicardial adipose tissue mass index (EAMI) was calculated as EAT volume divided by absolute value of the EAT attenuation index, measured using coronary computed tomography angiography (CTA). The relationship between EAMI and MACE was analyzed using Kaplan–Meier curves, Cox regression, and restricted cubic spline (RCS) plots. The predictive performance of EAMI was assessed through receiver operating characteristic (ROC) curves, C-index, net reclassification index (NRI), integrated discriminant improvement (IDI), coefficient of determination (R2), calibration curves, Brier score, and decision curve analysis (DCA) with comparisons to the GRACE score. Subgroup analyses were conducted based on age, gender, body mass index (BMI), left ventricular ejection fraction (LVEF), and culprit artery.ResultsA total of 308 patients were included in the analysis, with 212 in the training set and 96 in the validation set. In the training set, Kaplan–Meier survival analysis revealed that higher EAMI levels were associated with an increased cumulative risk of MACE. Cox multivariate regression analysis indicated that EAMI was independently associated with MACE (HR = 2.349, 95% CI 1.770–3.177, P < 0.001). Restricted cubic spline (RCS) analysis suggested a positive dose-response relationship between EAMI and MACE (P for nonlinearity = 0.87). EAMI showed better discriminative ability, prediction effect, accuracy, and clinical applicability compared to the traditional GRACE score. In the validation set, EAMI also demonstrated good predictive performance for MACE. Subgroup analyses suggested that EAMI's predictive ability was consistent across various demographic and clinical characteristics.ConclusionEAMI has high value in predicting MACE in patients 1-year after STEMI, helps identify high-risk patients with poor prognosis in early clinical practice.